Drug Treatment of Hypertension in Pregnancy - Brown, Catherine M. (Drugs, 2014)
Hypertensive disorders represent major causes of pregnancy related maternal mortality worldwide. Similar to the non-pregnant population, hypertension is the most common medical disorder encountered during pregnancy and is estimated to occur in about 6–8% of pregnancies [1]. A recent report highlighted hypertensive disorders as one of the major causes of pregnancy-related maternal deaths in the United States, accounting for 579 of the 4693 (12.3%) maternal deaths that occurred between 1998 and 2005 [2]. In low-income and middle-income countries, preeclampsia and its convulsive form, eclampsia, are associated with 10–15% of direct maternal deaths [3]. The optimal timing and choice of therapy for hypertensive pregnancy disorders involves carefully weighing the risk-versus-benefit ratio for each individual patient, with an overall goal of improving maternal and fetal outcomes. In this review we have compared and contrasted the recommendations in different treatment guidelines and we have outlined some newer perspectives on management. We have aimed to provide a clinically orientated guide to the drug treatment of hypertension in pregnancy.